Molecular epidemiological characteristics of Mycobacterium leprae in highly endemic areas of China during the COVID-19 epidemic - Zhou, Jiaojiao; Wu, Ziwei; Tong, Yi; Chokkakula, Santosh; Shi, Ying; Jiang, Haiqin; Liu, Jie; Wang, De; Zhang, Wenyue; Wang, Chen; Zhao, Tingfang; Yuan, Kang; et al. (Frontiers in Public Health, 2024)
Objectives: The present study analyzed the impact of the COVID-19 pandemic on the prevalence and incidence of new leprosy cases, as well as the diversity, distribution, and temporal transmission of Mycobacterium leprae strains at the county level in leprae-endemic provinces in Southwest China.Methods: A total of 219 new leprosy cases during two time periods, 2018-2019 and 2020-2021, were compared. We genetically characterized 83 clinical isolates of M. leprae in Guizhou using variable number tandem repeats (VNTR) and single nucleotide polymorphisms (SNPs). The obtained genetic profiles and cluster consequences of M. leprae were compared between the two periods.Results: There was an 18.97% decrease in the number of counties and districts reporting cases. Considering the initial months (January-March) of virus emergence, the number of new cases in 2021 increased by 167% compared to 2020. The number of patients with a delay of > 12 months before COVID-19 (63.56%) was significantly higher than that during COVID-19 (48.51%). Eightyone clinical isolates (97.60%) were positive for all 17 VNTR types, whereas two (2.40%) clinical isolates were positive for 16 VNTR types. The (GTA)9, (TA)18, (TTC)21 and (TA)10 loci showed higher polymorphism than the other loci. The VNTR profile of these clinical isolates generated five clusters, among which the counties where the patients were located were adjacent or relatively close to each other. SNP typing revealed that all clinical isolates possessed the single SNP3K.Conclusion: COVID-19 may have a negative/imbalanced impact on the prevention and control measures of leprosy, which could be a considerable fact for official health departments. Isolates formed clusters among counties in Guizhou, indicating that the transmission chain remained during the epidemic and was less influenced by COVID-19 preventative policies.